Gait abnormalities following slipped capital femoral epiphysis (Annals of Medical Research, 2021)
Aim: The aim of this study was to compare the gait function following slipped capital femoral epiphysis (SCFE) with the healthy controls.Material and Methods: We included 31 of 76 SCFE patients who were treated with in situ pinning between 2005 and 2013. We excluded patients with radiographic or clinical evidence of a contralateral slip, less than 2-years follow-up, incomplete epiphyseal closure, musculoskeletal abnormalities that can affect gait, avascular necrosis or chondrolysis and needed revision surgery. To measure the patients’ quality of life and physical function Harris hip score and the Pediatric Outcomes Data Collection Instruments (PODCI) scores were used. All patients and control group were underwent whole-body motion analysis.Results: The mean age of patients when gait analyses were performed was 16.5 ± 2.5 years, and mean body mass index (BMI) was 27.78 ± 5.6 kg/m2. A control group was formed from volunteers whose mean age was 17.84 ± 1.47 years that ranged between 16 and 20 years, with a mean BMI of 27.72 ± 2.61 kg/m2. Significant gait deviations were detected in SCFE patients such as (SCFE versus control group); Pelvis tilt range of motion (ROM) (3.5±1.5 - 2.3±0.5, p=0.01), Hip flexion ROM (35.1±3.7 - 39.8±4.6, p0.01), Pelvis obliquity ROM (5.5±2.3 - 9.5±2.8, p0.01), Hip abduction ROM (10.8±2.9 - 12.9±3.4, p=0.02), Knee Abduction ROM (15.2±6.1 - 10.7±6.9, p=0.01), Mean FPA (-11.1±7.7 - -5.2±6.5, p=0.01), Ankle rotation ROM (31.2±1.7 - 22.9±6.7, p=0.01), Mean thorax tilt (5.6±5.4 - 1.4±4.4, p0.01), Spine tilt ROM (5.1±3.3 - 7.8±3.4, p=0.02). Conclusion: Significant gait deviations were identified in patients with unilateral-SCFE in comparison with age and BMI matched healthy controls. Three-dimensional gait analysis can be used as an objective method for evaluation of functional outcomes of SCFE.
Keywords: Gait analysis; in situ fixation; slipped capital femoral epiphysis.